DIAGNOSIS OF FEMOROACETABULAR IMPINGEMENT SYNDROME - Michał Ciołkosz; Tomasz Antczak; Monika Gajda-Bathelt; Monika Dąbek; Katarzyna Jania; Zuzanna Perlicka; Karolina Smolińska; Paulina Sadkowska; Julia Kulczycka; Weronika Popow (International Journal of Innovative Technologies in Social Science, 2025)
Femoroacetabular impingement (FAI) syndrome is a frequent source of hip and groin pain in young and active populations. It arises from abnormal contact between the femoral head–neck junction and the acetabular rim, often due to cam, pincer, or mixed morphologies. Over time, this mechanical conflict can cause labral and cartilage damage, potentially leading to early osteoarthritis. Diagnosis requires a combination of patient history, physical examination, and imaging. While clinical impingement tests offer initial insights, they lack specificity and must be interpreted alongside radiographs and, when necessary, MRI. Parameters such as the alpha angle and acetabular coverage are key radiographic markers, but thresholds remain debated. Intra-articular anesthetic injections can help differentiate joint-related symptoms from other sources. Treatment options include conservative physiotherapy—focused on education, targeted exercise, and activity modification—as well as arthroscopic surgery, which aims to correct bony abnormalities and repair damaged tissue. Although surgical outcomes often show greater symptom improvement in the short and medium term, non-surgical care remains effective for many and avoids procedural risks.